2022
DOI: 10.1002/ijc.33885
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic alterations in circulating bile acid profiles in the development of hepatocellular carcinoma

Abstract: Bile acids (BAs) play different roles in cancer development. Some are carcinogenic and BA signaling is also involved in various metabolic, inflammatory and immune‐related processes. The liver is the primary site of BA synthesis. Liver dysfunction and microbiome compositional changes, such as during hepatocellular carcinoma (HCC) development, may modulate BA metabolism increasing concentration of carcinogenic BAs. Observations from prospective cohorts are sparse. We conducted a study (233 HCC case‐control pairs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…In the past decades, more investigations are emerging on the correlations between gut microbiota and hepatocellular carcinoma (HCC) [ 5 , 6 ]. The gut microbiota produces numerous metabolites in the human body, including lipopolysaccharides (LPS), short-chain fatty acids, and BAs, which could promote haptic inflammation, resulting in liver diseases such as liver fibrosis, liver cirrhosis, and HCC [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, more investigations are emerging on the correlations between gut microbiota and hepatocellular carcinoma (HCC) [ 5 , 6 ]. The gut microbiota produces numerous metabolites in the human body, including lipopolysaccharides (LPS), short-chain fatty acids, and BAs, which could promote haptic inflammation, resulting in liver diseases such as liver fibrosis, liver cirrhosis, and HCC [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies have also confirmed higher levels of specific bile acids (most frequently GCA, but also taurodeoxycholic acid, taurocholate, glycocholate, CDCA and cholic acid) in the serum or plasma of patients with HCC when compared to healthy controls[ 27 - 33 ]. However, there is some variability as to the underlying etiology of chronic liver disease predisposing to HCC in these cohorts and direct comparison of BA profiles amongst these etiologies has not been made.…”
Section: Using Bile Acid As a Clinical Tool In Patients With Or At Ri...mentioning
confidence: 93%
“…This study may indicate that an altered bile acid metabolism may have a role in developing HCC. 59 Under cholestatic conditions, conjugated bile acids can activate the S1PR2 and the AKT and ERK1/2 signaling pathways and play a critical role in promoting invasive growth of cholangiocarcinoma, as shown in the mouse model. 60 Primary sclerosing cholangitis (PSC) combined with inflammatory bowel disease (IBD) has a high risk of developing colon cancer with a cumulative risk of 50% after 25 years of illness, ie, 5-fold higher than in IBD without PSC, possibly due to exposure of the colon to toxic bile.…”
Section: Bile Acid Metabolism In Altered Conditionsmentioning
confidence: 98%